Modeling of direct recovery of lactic acid from whole broths by exchange adsorption - Sosa, Andrea Vanesa (2001)
Lactic acid fermentation process with L. casei CRL 686 was performed. The static adsorption isotherm over a strong anionic exchange resin, Amberlite IRA-400 was measured, and the static binding capacity parameters were quantified. Early recovery of lactic acid from this lactate producer from unclarified culture broth was performed in a liquid solid fluidized bed, with the resin as the solid adsorbent, and the dynamic adsorption capacity was calculated. Good agreement was found between static and dynamic binding capacity values. The fluidized bed height was twice the settled bed height and the overall process was controlled by the liquid solid mass transfer. This operation was also simulated by continuously well stirred tanks arranged in series and superficial solid deactivation as in a gas solid catalytic reactor. The deactivation process takes into account liquid channeling and agglomerations of solid induced by the viscosity of the broth and also by the cells during the adsorption. These patterns were also verified by experimental observations, and are in agreement with the results found in the literature. The breakthrough data together with others from previous works were satisfactorily fitted until the 90% dimensionless concentration was reached for both culture broths. The model could be used in future studies on predictions about the liquid solid fluidized bed behavior and other different operating conditions.